2005
DOI: 10.1016/j.jvs.2004.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous angioplasty and stenting of the superficial femoral artery

Abstract: PTA and stenting of the SFA can be performed safely with excellent procedural success rates. Improved patency of these interventions was seen with increased ankle/brachial index and the performance of angioplasty only. Worse patency was seen with TASC C and TASC D lesions. Patency rates were strongly dependent on lesion type, and the results of angioplasty and stenting compared favorably with surgical bypass for TASC A and B lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
145
2
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(164 citation statements)
references
References 15 publications
8
145
2
8
Order By: Relevance
“…Long segment stenosis, small diameter of the stent, metal composition, thrombogenecity and rigidity of the stent negatively affect the patency and may promote myointimal hyperplasia, restenosis and thrombosis [4,5]. Myointimal hyperplasia usually occurs in the transition zone between stent and the artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long segment stenosis, small diameter of the stent, metal composition, thrombogenecity and rigidity of the stent negatively affect the patency and may promote myointimal hyperplasia, restenosis and thrombosis [4,5]. Myointimal hyperplasia usually occurs in the transition zone between stent and the artery.…”
Section: Discussionmentioning
confidence: 99%
“…The post-operative course was uneventful. The patient was discharged with oral klopidogrel and acetylsalicylic acid on post-operative [4]. day with palpable distal pulses.…”
Section: Case Reportmentioning
confidence: 99%
“…Other studies have reported the results of bail-out stenting strategies (stenting performed if only angioplasty alone fails) which reveal a mean primary patency rate of 55% at 12 months [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Other advantages of pursuing immediate angiography in patients with acute limb ischemia include delineation of the limb arterial anatomy with visualization of both inflow and runoff vessels. Complete aortogram with runoffs should be obtained prior to intervening with occlusive lesions, as short-and long-term patency and clinical success are dependent on the outflow status 10) . During the acute stage of disease, when thrombus is visible on an aortogram, early intervention such as PTA or stent insertion may lead to distal embolic events.…”
Section: Discussionmentioning
confidence: 99%